KERJA SAMA BILATERAL INDONESIA-AUSTRALIA MELALUI BUDAYA TENUN KHAS LOMBOK, NTB TAHUN 2017-2019 - Nirwana Hidayati, Siti Husni; Putri, Penny Kurnia; Sushanti, Sukma (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
The main objective of this study is to find out how the bilateral cooperation between the Indonesian and Australian governments is carried out through the weaving culture of Lombok, NTB. This study uses a descriptive qualitative method to analyze the process of cooperation on the issues raised. The concept used is bilateral cooperation and trade agreements, which later obtained the result that bilaterally Indonesia made various efforts to promote Lombok Weaving products. This study focuses on the interaction of bilateral cooperation between Indonesia and Australia by using the Free Trade Agreement concept. This was done because we saw a good increase in woven products which was able to provide various achievements in several fields, especially in the economic field, both progress in preserving the value of a culture. The concept of a Free Trade Agreement is believed to be an easier way to carry out a cooperation between countries. Key Word: Bilateral Cooperation, Free Trade Agreement, Indonesia-Australia Lombok Weaving, Trade Agreement